From Transactional Compliance to Judicial Justice: (Answering the Challenges of Sharia Economics and Contemporary Law Enforcement) - Zulhamdi Zulhamdi (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This edition of Al-Hiwalah: Journal of Islamic Economic Law presents ten scientific articles that comprehensively examine the dynamics of Islamic economic law, judicial jurisprudence, and the protection of vulnerable groups in Indonesia. In the muamalah cluster, the manuscript dissects sustainable regional investment policies in South Kalimantan, a normative analysis of DSN-MUI Fatwa No. 115/2017 regarding the integration of the principle of Al-Ghunm bi Al-Ghurm and the prohibition of Dhaman in mudharabah, and the resolution of insurance disputes at PT. Asuransi Takaful Indonesia. Empirical aspects are explored through transactions at Fadel Dela Buli Market, Maba District, as well as the perception of zakat management by the Al-Mutathahirin Mosque Council in Ternate. Meanwhile, the realm of family law and law enforcement focuses analysis on the decisions of the Sukoharjo Religious Court, including the judge's considerations in determining child custody after divorce (No. 708/Pdt.G/2025/PA.Skh), domestic violence as a basis for divorce (No. 223/Pdt.G/2023/PA.Skh), and the legality of marriage confirmation (No. 16/Pdt.P/2025/PA.Skh). This discourse is strengthened by a comparative study of the Aceh MPU Fatwa No. 18/2015 and the MUI Fatwa No. 11/2012 regarding illegitimate children from the perspective of Maqasid Syariah, as well as an analysis of the structural obstacles to the enforcement of Law No. 12 of 2022 concerning Sexual Violence. This edition successfully bridges the dogmatics of legal texts with socio-economic realities, while formulating applicable policy recommendations for academics, judicial practitioners, and national policymakers